First Aid Overview of Primary School Teachers to Students with Epistaxis: EPISTAXIS - Firjatullah, Yusuf Muhammad; Mulyadi, Arif; Bermudez, Roy Fabrigas (Health Access Journal, 2024)
Epistaxis often occurs in elementary school aged children. Teachers are the people closest to students and are the first aid to children who experience epistaxis at school. This research aims to identify the ability of MI Manba ul' Ulum Tulungagaung teachers in providing first aid treatment for students with epistaxis. This research used a quantitative descriptive method with a population of all teachers who teach at MI Manba 'Ul 'Ulum Tulungagaung as many as 36 teachers, all of whom are samples in this research using analytical techniques. The results of this study indicate that more than half of the teachers at MI Manba 'Ul 'Ulum Tulungagung's epistasis first aid abilities (52.8percent) are sufficient and less than half (25percent) are less than half (22.2percent) have sufficient abilities. good abilities. Therefore,teachers with sufficient and inadequate skills regarding first aid for epistaxis should increased their knowledge and skills so that they can perform first aid for epistaxis correctly, namely collaborating with community health centers to provide education about first aid, especially epistaxis, in the UKS (School Health Unit).